Assessment and practical application of mapping algorithms for beam elements in computational FSI - Wang, Tianyang; Wüchner, Roland; Bletzinger, Kai-Uwe (European Journal of Computational Mechanics, 2016)
If a beam structure is modelled by 1D finite elements in a fluid–structure interaction (FSI) simulation, due to dimensional reduction in beam theory, the actual structural surface is not available which results in non-matching discrete geometries of the FSI interface. A linearised and a co-rotating algorithms applying the corresponding beam kinematics are proposed in another work to map deformation and load between the 1D beam mesh and the 2D surface mesh. In this work, the convergence behaviour of both algorithms is assessed with analytically described deformation. Besides, efficient treatments for both structured and unstructured fluid wet-surface meshes as well as treatment for connected beams are introduced as a practical extension to the core algorithm. Moreover, mapping is applied in the FSI simulation of a wind turbine where the rotor blades are modelled by beam elements.